PENINGKATAN EKONOMI MASYARAKAT MELALUI KOPERASI SIMPAN PINJAM SYARIAH BMT AL HASANAH SEKAMPUNG - Umi Mahmudah (Journal Tafkirul Iqtishodiyyah, 2024)
Sharia cooperatives focus more on collecting and distributing non-profit funds, such as zakat, infaq, alms. This type of research uses qualitative research with a descriptive approach. BMT Al Hasanah Fund Savings and Loans Cooperative in implementing its sharia-based products, namely fund-raising products such as: Daily savings, term savings. And the distribution of funds such as murabahah financing, mudharabah financing, ar-rahn financing in the community has made a contribution that can improve the standard of living of small communities. 2. The efforts or steps taken by the BMT Al Hasanah Fund Savings and Loans Cooperative in overcoming the problem of poverty, namely implementing the sharia system in providing capital assistance to the community through its products, and also the cooperative has a marketing strategy in collecting funds to increase capital